2009
DOI: 10.1115/1.2982137
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Performance of Biodiesel and Diesel-Vegetable Oil Blends in a Simulated Gas Turbine Burner

Abstract: Recent increases in fuel costs, concerns for global warming, and limited supplies of fossil fuels have prompted wide spread research on renewable liquid biofuels produced domestically from agricultural feedstock. In this study, two types of biodiesels and vegetable oil (VO) are investigated as potential fuels for gas turbines to generate power. Biodiesels produced from VO and animal fat were considered in this study. The problems of high viscosity and poor volatility of VO (soybean oil) were addressed by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Firstly, the evaporation behavior as well as the combustion kinetics of vegetable oil and diesel fuel are similar. The differences in fuel composition will therefore have only minor effects, as was concluded by Panchasara et al [37] after experiments in an atmospheric pressure burner. This leaves the atomization quality as the main factor influencing the combustion of this biofuel, which is dominated by the viscosity in the tested fuel temperature range [30,31].…”
Section: Fuel Propertiesmentioning
confidence: 76%
“…Firstly, the evaporation behavior as well as the combustion kinetics of vegetable oil and diesel fuel are similar. The differences in fuel composition will therefore have only minor effects, as was concluded by Panchasara et al [37] after experiments in an atmospheric pressure burner. This leaves the atomization quality as the main factor influencing the combustion of this biofuel, which is dominated by the viscosity in the tested fuel temperature range [30,31].…”
Section: Fuel Propertiesmentioning
confidence: 76%
“…There have been reports from several groups that applied biomass-derived alternative fuel using liquid swirl flame burners (Hashimoto et al, 2008;Panchasara et al, 2009) and industrial gas turbines (Moli ere et al, 2007;Liu et al, 2009). Hashimoto et al (2008 reported lower NO x emission for palm biodiesel compared to diesel under gas turbine operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The interest of applying biodiesel in gas turbine largely stems from the merits of renewability, sulphur-free and potentially cleaner combustion. However, due to differences in quality of biodiesel depending on feedstock, rigorous testing have to be performed to characterise the spray, combustion and emission performance to ensure the suitability and reliability of biodiesel in gas turbine.There have been reports from several groups that applied biomass-derived alternative fuel using liquid swirl flame burners (Hashimoto et al, 2008;Panchasara et al, 2009) and industrial gas turbines (Moli ere et al, 2007;Liu et al, 2009). Hashimoto et al (2008 reported lower NO x emission for palm biodiesel compared to diesel under gas turbine operating conditions.…”
mentioning
confidence: 99%
“…These prior studies considered overall emissions for biofuels relative to conventional practical fuels, without detailed characterisation of the swirl spray droplet transport and trajectories, flow fields and flame reaction zones [6,7]. Spray flames involve the complex interaction of air, fuel and chemistry that results in the simultaneous heat, mass and momentum transfer in addition to chemical reaction.…”
Section: Introductionmentioning
confidence: 99%